TRANSFORMASI SOSIAL- BUDAYA MASYARAKAT ARAB PADA MASA RASULULLAH SAW: ANALISIS HISTORIS - Roihan, Siti; Zen, Nurzena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Muhammad SAW initiated a systematic upheaval that altered tribal allegiances into a broader sense of brotherhood (Ukhuwah Islamiyah). This change involved the removal of oppressive social hierarchies, the advancement of women's roles, and the establishment of a fair legal framework. Additionally, a major cultural transition took place, moving from violent traditions toward a community that values high moral standards (Akhlakul Karimah). The research concludes that these changes effectively transformed the fragmented Arab community into a cohesive and civilized entity. These developments laid the essential groundwork for the emergence of Islamic civilization, which harmonizes religious and humanistic elements. The successful nature of this transformation demonstrates that Islamic principles were effective in enabling a profound social reformation in a relatively brief timeframe, transforming a nomadic society into one with a vision for global civilization.